2017
DOI: 10.1093/ejcts/ezx131
|View full text |Cite
|
Sign up to set email alerts
|

Aortic diameter remodelling after the frozen elephant trunk technique in aortic dissection: results from an international multicentre registry†

Abstract: The FET technique provides an effective treatment for AoD, promoting FL thrombosis and remodelling in the descending thoracic aorta. Changes in the diameter of the aortic lumen depend mainly on the status of the FL and are similar between acute and chronic AoD. Changes in the diameter of true lumen are affected by both the FL status and the timing of the presentation. However, increased FL thrombosis and positive remodelling rates are not maintained at the level of the abdominal aorta, and strict follow-up is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 17 publications
8
66
0
Order By: Relevance
“…A recent study has found that at the time of initial repair for TAAD in MFS, a more aggressive surgical approach seems to be superior to limited repair (29). However, there is scarce data on the long-term outcomes of such extensive repair for TAAD in such patients (19,22,30). The current cohort expanded the special subset of MFS patients in our experience (17,22,31), who, following a prior Bentall procedure, developed TAAD involving the arch, which was repaired in a reoperative setting with the extensive FET technique.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that at the time of initial repair for TAAD in MFS, a more aggressive surgical approach seems to be superior to limited repair (29). However, there is scarce data on the long-term outcomes of such extensive repair for TAAD in such patients (19,22,30). The current cohort expanded the special subset of MFS patients in our experience (17,22,31), who, following a prior Bentall procedure, developed TAAD involving the arch, which was repaired in a reoperative setting with the extensive FET technique.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in acute aortic dissection, a progressive false lumen thrombosis, seen in more than 90% of patients, followed by shrinkage and positive remodelling, has been reported from several studies. 162,163 The potential exclusion of the downstream aortic pathology occurs predominantly up to the distal end of the stent graft, so that FET can be applied curatively only in association with the extension of…”
Section: Frozen Elephant Trunk Techniquementioning
confidence: 99%
“…No consensus exists about which parameter or parameters (diameter, area, volume, or absolute ratio between the two lumina) should be used to define aortic remodeling (10,(51)(52)(53). Some investigators proposed use of a 10% volumetric difference to define substantial changes in aortic size, also known as remodeling (52,54).…”
Section: Remodeling Remodeling Definitionmentioning
confidence: 99%